Quality of service performances of video and voice transmission in universal mobile telecommunications system network based on OPNET - Sameer A. S. Lafta; Mohaned Mahdi Abdulkareem; Raed Khalid Ibrahim; Marwah M. Kareem; Adnan Hussein Ali (Bulletin of Electrical Engineering and Informatics, 2021)
The universal mobile telecommunications system (UMTS) has distinct benefits in that it supports a wide range of quality of service (QoS) criteria that users require in order to fulfill their requirements. The transmission of video and audio in real-time applications places a high demand on the cellular network, therefore QoS is a major problem in these applications. The ability to provide QoS in the UMTS backbone network necessitates an active QoS mechanism in order to maintain the necessary level of convenience on UMTS networks. For UMTS networks, investigation models for end-to-end QoS, total transmitted and received data, packet loss, and throughput providing techniques are run and assessed and the simulation results are examined. According to the results, appropriate QoS adaption allows for specific voice and video transmission. Finally, by analyzing existing QoS parameters, the QoS performance of 4G/UMTS networks may be improved.